Percutaneous epicardial pacing using a novel transverse sinus device. (6th July 2018) - Vaidya, Vaibhav R.; Sugrue, Alan; Padmanabhan, Deepak; Killu, Ammar M.; Naksuk, Niyada; Al‐Masry, Anas Abudan; Isath, Ameesh; Pedersen, Joanne; Yngsdal, Lisa; Ladewig, Dorothy J.; Friedman, Paul A.; Asirvatham, Samuel J.
Abstract: Background: Transvenous lead implantation has multiple drawbacks and complications that can be overcome by epicardial lead placement. We aimed to design percutaneously implanted epicardial leads that are anchored through the transverse sinus (TS). Methods and results: We designed a novel multielectrode pacing device with four bipole electrode pairs. The device is advanced through the TS, with both ends externalized out of the pericardium. We tested the prototype in one proof‐of‐concept and 5 additional acute canine experiments. The TS device recorded ventricular and atrial electrograms. The median amplitude of near‐field ventricular electrograms was 3.3 mA (IQR 2.0–4.3) and of near‐field atrial electrograms was 2.1 mA (IQR 1.3–2.2). The median ventricular threshold (N  =  30) was 1.1 mA (IQR 0.7–3.1) at a median pulse width of 0.5 ms (IQR 0.5–0.5). The median atrial threshold (N  =  10) was 2.4 mA (IQR 1.1–7.8) at a median pulse width of 0.5 ms (IQR 0.5–0.9). Right and left ventricular and atrial pacing morphologies were noted while pacing electrodes adjacent to these chambers. Simultaneous left (LV) and right ventricular (RV) pacing showed reduction in QRS duration from 116 ms (RV) and 105 ms (LV) to 91 ms. On necropsy, the device was located in the TS in all animals. There were TS abrasions in one animal, and no other acute complications. Conclusions: This study highlights a novel approach to epicardial pacing harnessing the unique anatomy of the transverse sinus as an anchoring point. Placement of this novel transverse sinus device was safe and feasible, with acceptable atrial and ventricular thresholds.